What is new about ovarian malignancies? - Grabska, Kinga; Pilarska, Izabela; Magdalena Fudalej, Marta; Deptała, Andrzej; Badowska-Kozakiewicz, Anna (Contemporary Oncology/Współczesna Onkologia, 2021)
Ovarian cancer is one of the most prevalent pathologies in gynaecology. This malignancy can be divided into 2 large groups: epithelial and non-epithelial. Because epithelial ovarian cancers (EOC) are the most commonly diagnosed, this paper focuses on the latest therapies associated with this disease. Due to the difficult diagnosis, EOC is frequently detected in the advanced stage. The treatment is usually complex and requires specialist knowledge. Advances and new ideas, such as identification of various genes and molecules that can serve as prognostic factors, might increase patients’ chances of survival; they may contribute to optimization of patients’ treatment, deciding whether to use aggressive treatment strategies, and predicting chemoresistance. Moreover, new strategies might also improve the quality of life of patients. The study aimed to analyse and discuss the latest reports on new methods of managing EOC.